MUHAMMADIYAH'S INSIGHT ON TOLERANCE AS CONTAINED IN THE RISALAH ISLAM BERKEMAJUAN - Qorib, Muhammad (Berajah Journal, 2024)
Diversity is God's blueprint and therefore must be accepted and addressed properly. Today, everyone everywhere cannot escape interaction with others. Therefore, cultural encounters are a necessity. In this context, tolerance becomes very important. Tolerance is a guideline for how each person interprets his or her presence together with others. This paper aims to explore Muhammadiyah's insights on tolerance as contained in the book Risalah Islam Berkemajuan. This research is a library research. Primary data in this research is taken from the Manuscript of the Risalah Islam Berkemajuan. Secondary data in this research is taken from Muhammadiyah ideological texts related to tolerance. This research shows that Muhammadiyah's insights on tolerance are contained in the Manuscript of Risalah Islam Berkemajuan. The insight can be seen from the Muhammadiyah movement, namely; da'wah movement, tajdid movement, science movement, charity movement. The services performed by Muhammadiyah also show that insight, such as humanitarian services and global services.